Epidemiological features and trends in the mortality rates of 10 notifiable respiratory infectious diseases in China from 2004 to 2020: Based on national surveillance - Zhao, Na; Wang, Supen; Wang, Lan; Shi, Yingying; Jiang, Yixin; Tseng, Tzu-Jung; Liu, Shelan; Chan, Ta-Chien; Zhang, Zhiruo (Frontiers in Public Health, 2023)
Objectives: The aim of this study was to describe, visualize, and compare the trends and epidemiological features of ten notifiable respiratory infectious diseases mortality in China from 2004 to 2020. Setting: Data were obtained from the database of the National Infectious Disease Surveillance System (NIDSS), and reports released by the National and local Health Commissions from 2004 to 2020. Spearman correlations and Joinpoint regression models were used to quantify the temporal trends of RIDs by calculating annual percentage changes (APCs) of the mortality. Results: Overall mortality of RIDs was stable across China from 2004 to 2020 (R = -0.38, P = 0.13), with an APC per year of -2.2% (95% CI: -4.6 to 0.3; P = 0.1000). However, the overall mortality rate of ten RIDs in 2020 decreased by 31.80% (P = 0.006) compared to the previous five years before-COVID-19 stage. The highest mortality occurred in northwestern, western, and northern China. Tuberculosis was the leading cause of RIDs mortality, and mortality from tuberculosis was relatively stable in the past 17 years (R = -0.36, P = 0.16), with APC of -1.9% (95% CI -4.1 to 0.4, P = 0.1000). Seasonal influenza was the only causes which mortality significantly increased (R = 0.73, P = 0.00089), with APC of 29.70% (95% CI 16.60% to 44.40%; P = 0.0000). The highest yearly case-fatality ratios (CFR) were avian influenza A H5N1 [687.5 per 1000 (33/48)] and epidemic cerebrospinal meningitis [90.5748 per 1000 (1 010/11 151)]. Age-specific CFR of ten RIDs was highest among people older than 85-year-old [13.6551 per 1 000 (2 353/172 316)], and was lowest among children younger than 10 years, particularly in 5-year-old children [0.0552 per 1 000 (58/1 051 178)]. Conclusions: Mortality rates of ten RIDs were relatively stable during 2004- 2020, while with large differences among Chinese provinces and age group. There was an increase trend in mortality for seasonal influenza. Concerted efforts are needed to reduce the mortality of seasonal influenza in the future.